Flexible metal-clad laminate with microstrip line structure

By using a polyimide film with a thickness of 75 to 200 μm and a thermoplastic/non-thermoplastic multilayer structure in the flexible metal-covered laminated plate, the low transmission loss of the microstrip line structure is achieved, and the flexible metal-covered laminated plate in the prior art is solved. The problem of high transmission loss is suitable for high-speed and high-frequency applications.

CN114929474BActive Publication Date: 2025-01-07KANEKA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180008908.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-02
Filing Date
2021-01-27
Publication Date
2025-01-07
Estimated Expiration
2041-01-27

AI Technical Summary

Technical Problem

The prior art is difficult to achieve low transmission loss of flexible metal-covered laminated plates. There are limits to low dielectric constant and low dielectric loss of polyimide, and it is impossible to further reduce the transmission loss of flexible metal-covered laminated plates.

Method used

A polyimide film with a thickness of 75 to 200 μm was used to form a flexible metal laminated plate with a microstrip line structure. Through a multi-layer structure of thermoplastic and non-thermoplastic polyimide layers, the dielectric loss at 10 GHz was controlled to be less than 0.008. , achieve low transmission loss.

Benefits of technology

It realizes low transmission loss of flexible metal-covered laminated plates, is suitable for high-speed and high-frequency transmission lines, is suitable as a coaxial cable and antenna material, reducing signal transmission loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114929474B_ABST
    Figure CN114929474B_ABST
Patent Text Reader

Abstract

The subject of the invention of the present application is to achieve a further reduction in transmission loss of a flexible metal-clad laminate. The invention of the present application can solve the above-mentioned problem by using a flexible metal-clad laminate, wherein the flexible metal-clad laminate is characterized in that it has a microstrip line structure, and the flexible metal-clad laminate has at least a signal line (3) / a first polyimide layer (2) / a ground layer (1) in this order, wherein the thickness of the first polyimide layer (2) is 75 to 200 μm and the dielectric loss at 10 GHz is less than 0.008.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a flexible metal-clad laminated board with a microstrip line structure. Background Art

[0002] Polyimide films are excellent in mechanical strength, heat resistance, electrical insulation, and chemical resistance, and are therefore widely used in electronic substrate materials. For example, polyimide films are used as substrate materials to manufacture flexible copper-clad laminates (hereinafter, also referred to as FCCL) having copper foil laminated on at least one side, and flexible printed circuit boards (hereinafter, also referred to as FPC) having circuits, and the like, which are used in various electronic devices.

[0003] With the high-speed signal transmission of electronic equipment in recent years, in the high-frequency of the electrical signal transmitted in the circuit, the requirement of low dielectric constant and low dielectric loss tangent of polyimide as substrate material is improving. The tendency of high frequency is progressing, and in the future, it is required that the dielectric constant and dielectric loss tangent are also low in such regions as more than 5GHz and more than 10GHz. And then the propagation speed of the signal in the electronic circuit will reduce when the dielectric constant of the substrate material increases. If dielectric constant and dielectric loss tangent increase in addition, the transmission loss of the signal also increases. Therefore, it is important for the high performance of electronic equipment that the low dielectric constant of polyimide as substrate material, low dielectric loss tangent, and then the transmission loss under the state of making FPC is small.

[0004] As a film suitable for use in high-frequency circuit substrates, an insulating resin layer in which a resin powder with a low dielectric constant is mixed in a polyimide resin is known. For example, Patent Document 1 discloses an example in which a polyimide containing fine powder of a fluorine-based resin is used in a circuit substrate.

[0005] In addition, Patent Document 2 states that it is effective to lower the dielectric constant and dielectric loss of polyimide as a substrate material. As representative methods for wiring high-speed transmission lines in FPC, strip lines and microstrip lines are known. The structure of the microstrip line is simple, and the transmission line is wired on the surface layer of the substrate, so the signal characteristics are excellent and it can be manufactured inexpensively. In addition, the strip line is covered by two GND planes, so it has the characteristic of being able to suppress electromagnetic interference (EMI) compared to the microstrip line. In recent years, the demand for low transmission characteristics among various characteristics is becoming stronger, and the use of microstrip lines with excellent transmission characteristics is increasing. On the other hand, it is recorded that in order to reduce transmission loss by using strip lines, it is effective to lower the dielectric constant and dielectric loss of polyimide as a substrate material (Patent Document 2).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Publication No. 2017-78102

[0009] Patent Document 2: Japanese Patent Publication No. 2018-145303 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] However, Patent Document 2 only involves reducing the dielectric loss of polyimide as a substrate material as a means of reducing transmission loss, and cannot achieve further low transmission loss of the flexible metal-clad laminate. There is a limit to the low dielectric constant and low dielectric loss of polyimide. In order to achieve further low transmission loss of the flexible metal-clad laminate, it is a problem to provide a method for manufacturing a flexible metal-clad laminate and a flexible metal-clad laminate with low transmission loss.

[0012] Solutions for solving problems

[0013] The present inventors have conducted intensive research and found that the above-mentioned problems can be solved by the following configuration. That is, the present invention is formed as follows.

[0014] One embodiment of the present invention relates to a flexible metal-clad laminate, characterized in that it has a microstrip line structure, wherein the flexible metal-clad laminate has at least a signal line / a first polyimide layer / a ground layer in sequence, the thickness of the first polyimide layer is 75 to 200 μm and the dielectric loss at 10 GHz is less than 0.008.

[0015] In addition, one embodiment of the present invention relates to a method for manufacturing a flexible metal-clad laminate, characterized in that it is a method for manufacturing a flexible metal-clad laminate having a microstrip line structure, wherein the flexible metal-clad laminate has at least a signal line / a first polyimide layer / a ground layer in sequence, and as the first polyimide layer, a polyimide film having a thickness of 75 to 200 μm and a dielectric loss of less than 0.008 at 10 GHz is used.

[0016] Effects of the Invention

[0017] According to the present invention, a method for manufacturing a flexible metal-clad laminate capable of simply preventing transmission loss of the flexible metal-clad laminate and a flexible metal-clad laminate with low transmission loss can be provided. The flexible metal-clad laminate can be suitably used as a coaxial cable replacement for flexible applications requiring high-speed and high-frequency transmission lines and antenna applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the cross section of a flexible metal-clad laminate with microstrip lines.

[0019] Figure 2 Schematic cross-sectional view of a flexible metal-clad laminate having a microstrip line with a plurality of signal lines.

[0020] Figure 3 This is a schematic diagram showing an example of a method for manufacturing a flexible metal-clad laminate having a microstrip line.

[0021] Figure 4 Schematic diagram of a cross section of a flexible metal-clad laminate with strip lines.

[0022] Figure 5 Schematic diagram of a cross section of a flexible metal-clad laminate with strip lines.

[0023] Figure 6 Schematic diagram of a cross section of a flexible metal-clad laminate with strip lines.

[0024] Figure 7 The present invention is a schematic diagram showing a method for manufacturing a flexible metal-clad laminate having strip lines.

[0025] Figure 8 This is a schematic diagram showing a lamination method of polyimide adhesive sheets.

[0026] Fig. 9 Schematic diagram showing a method for producing a single-sided flexible metal-clad laminate used in a flexible metal-clad laminate.

[0027] Fig.10 Schematic diagram showing a method for producing a single-sided flexible metal-clad laminate used in a flexible metal-clad laminate.

[0028] Fig.11 Schematic diagram showing a method for producing a single-sided flexible metal-clad laminate used in a flexible metal-clad laminate.

[0029] Fig.12 Schematic diagram showing a method for producing a double-sided flexible metal-clad laminate used in the flexible metal-clad laminate.

[0030] Fig.13 Schematic diagram showing a method for producing a double-sided flexible metal-clad laminate used in the flexible metal-clad laminate. DETAILED DESCRIPTION

[0031] The flexible metal-clad laminate of the present invention is characterized in that it has a microstrip line structure, and the flexible metal-clad laminate has at least a signal line / a first polyimide layer / a ground layer in this order, the thickness of the first polyimide layer is 75 to 200 μm and the dielectric loss at 10 GHz is less than 0.008.

[0032] In addition, the flexible metal-clad laminate of the present invention also has a ground layer / second polyimide layer / adhesive layer, and at least has a ground layer / second polyimide layer / adhesive layer / signal line / first polyimide layer / ground layer in sequence, the thickness of the aforementioned second polyimide layer is 75 to 200 μm and the dielectric loss at 10 GHz can be less than 0.008.

[0033] It should be noted that, in the present application specification, “a flexible metal-clad laminate having a microstrip line structure” refers to “a flexible metal-clad laminate having at least a signal line / a first polyimide layer / a ground layer in this order”. In addition, “a flexible metal-clad laminate having a stripline structure” refers to “a flexible metal-clad laminate having at least a ground layer / a second polyimide layer / an adhesive layer / a signal line / a first polyimide layer / a ground layer in this order”.

[0034] First, the polyimide film used in the first polyimide layer and the second polyimide layer of the present invention is described. The thickness of the polyimide film used in the first polyimide layer and the second polyimide layer is 75 to 200 μm and the dielectric loss at 10 GHz is 0.008 or less. By using the polyimide film, the insertion loss at 10 GHz of the flexible metal-clad laminate with a microstrip line structure and the flexible metal-clad laminate with a stripline structure can be made not less than -3.2 dB and not more than 0 dB.

[0035] It is preferred that the first polyimide layer has a thermoplastic polyimide layer and a non-thermoplastic polyimide layer, or that the first polyimide layer and the second polyimide layer each have a thermoplastic polyimide layer and a non-thermoplastic polyimide layer, because a flexible metal-clad laminate can be easily produced.

[0036] The polyimide film used in each of the first polyimide layer and the second polyimide layer is not particularly limited as long as the thickness is 75 to 200 μm and the dielectric loss at 10 GHz is less than 0.008. On the other hand, it is preferred to use a polyimide film having a multilayer structure of three layers with thermoplastic polyimide layers on both sides of a non-thermoplastic polyimide layer. In this case, compared with the case of a monolayer polyimide, although the number of laminating steps increases, there is a tendency to reduce the total manufacturing cost of the film, so it is ideal.

[0037] As the polyimide film used in each of the first polyimide layer and the second polyimide layer, the following film is particularly preferred. That is, at least two or more polyimide films having a three-layer structure with a thermoplastic polyimide layer on both sides of a non-thermoplastic polyimide layer and a thickness of less than 75 μm are laminated (compressed) to form a film with a thickness of 75 to 200 μm. This is ideal because the total manufacturing cost of the film can be reduced to the greatest extent.

[0038] (Polyimide adhesive sheet: a polyimide film having a three-layer structure in which a thermoplastic polyimide layer is provided on both sides of a non-thermoplastic polyimide layer)

[0039] Below, the polyimide film with 3-layer structure possessing thermoplastic polyimide layer on the two sides of non-thermoplastic polyimide layer is described.For convenience, the polyimide film with 3-layer structure possessing thermoplastic polyimide layer on the two sides of non-thermoplastic polyimide layer is called polyimide adhesive sheet.First, the raw material monomer of the polyamic acid of the precursor of the non-thermoplastic polyimide used in the non-thermoplastic polyimide layer, the manufacture of the polyamic acid of the precursor of the aforementioned non-thermoplastic polyimide, the manufacture method of the non-thermoplastic polyimide film, the order of the thermoplastic polyimide layer are described in detail.

[0040] (Raw material monomer of polyamic acid as a precursor of non-thermoplastic polyimide)

[0041] As the raw material monomer of the polyamic acid which is the precursor of the non-thermoplastic polyimide in the present invention, there is no particular restriction as long as the non-thermoplastic polyimide formed by imidizing the polyamic acid as the precursor satisfies the following requirements. That is, as long as the aforementioned non-thermoplastic polyimide has the solder heat resistance, dimensional stability, and flame retardancy required for the previous flexible printed circuit board material, and the aforementioned solder heat resistance, dimensional stability, and flame retardancy can be controlled by a primary structure and a manufacturing method, there is no particular restriction. As the aforementioned raw material monomer, for example, diamines and acid dianhydrides commonly used in the synthesis of polyamic acid can be used.

[0042] The diamine is not particularly limited as long as the effects of the present invention can be exhibited, and examples thereof include 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 4,4'-oxydiphenylamine, 3,3'-oxydiphenylamine, 3,4'-oxydiphenylamine, 4,4'-diaminodiphenyldiethylsilane, 4,4'-diaminodiphenylsilane, 4,4'-diaminodiphenylethylphosphine oxide, 4,4'-diaminodiphenylamine ... 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 2,2-bis(4-aminophenoxyphenyl)propane, and the like. These may be used alone or in combination.

[0043] Examples of diamines useful for achieving low dielectric loss include aliphatic diamines having 36 carbon atoms, 1,4-diaminobenzene (p-phenylenediamine), 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 4,4'-diamino-p-terphenyl, bis(4-aminophenyl)terephthalate, 2,2-bis(4-aminophenoxyphenyl)propane, 2,2-bis(4-aminophenoxyphenyl)hexafluoropropane, and 4,4'-bis(4-aminophenoxy)biphenyl. These diamines are preferably contained in an amount of 30 to 100 mol %, more preferably 50 to 100 mol %, and even more preferably 70 to 100 mol % in the total diamine component.

[0044] In addition, there are no particular restrictions on the acid dianhydride compounds that can be used as raw material monomers of the polyamic acid as long as the effects of the present invention can be exhibited, and examples thereof include pyromellitic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 4,4'-oxydiphthalic dianhydride, 3,4'-oxydiphthalic dianhydride, 2,2-bis(3 ,4-dicarboxyphenyl)propane dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)propane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)ethane dianhydride, oxydiphthalic dianhydride, bis(3,4-dicarboxyphenyl)sulfonic dianhydride, p-phenylene bis(trimellitic acid monoester anhydride), ethylene bis(trimellitic acid monoester anhydride), bisphenol A bis(trimellitic acid monoester anhydride) and their analogs, etc.

[0045] Examples of acid dianhydrides useful for achieving low dielectric loss include 3,3',4,4'-biphenyltetracarboxylic dianhydride, p-phenylenebis(trimellitic anhydride), 4,4'-oxydiphthalic dianhydride, 2,2'-bis(4-(3,4-dicarboxyphenoxy)phenyl)propane dianhydride, and pyromellitic dianhydride. These acid dianhydrides are preferably contained in an amount of 30 to 100 mol %, more preferably 50 to 100 mol %, and even more preferably 70 to 100 mol % in the total amount of the acid dianhydrides.

[0046] The first polyimide layer and the second polyimide layer can be manufactured, for example, by the following method. That is, the first polyimide layer and the second polyimide layer can be manufactured by using the diamine and the acid dianhydride as raw materials, performing a ring-opening addition polyreaction in a solvent, thereby obtaining a polyamic acid solution, and then heating the polyamic acid to perform a dehydration cyclization reaction (imidization). Thus, the dielectric loss of the first polyimide layer and the second polyimide layer at 10 GHz can be controlled to be within a range of 0.008 or less.

[0047] (Production of polyamic acid as a precursor of non-thermoplastic polyimide)

[0048] As the organic solvent used in the manufacture of the polyamic acid as a precursor of the non-thermoplastic polyimide, any solvent can be used as long as it is a solvent that dissolves the non-thermoplastic polyamic acid. For example, preferred amide solvents are N, N-dimethylformamide, N, N-dimethylacetamide, N-methyl-2-pyrrolidone, etc., and N, N-dimethylformamide and N, N-dimethylacetamide can be used more preferably. The solid content concentration of the polyamic acid as a precursor of the non-thermoplastic polyimide is not particularly limited. When it is within the range of 5% by weight to 35% by weight, a polyamic acid as a precursor of the non-thermoplastic polyimide having sufficient mechanical strength when a non-thermoplastic polyimide film is made can be obtained.

[0049] The order of adding the aromatic diamine and aromatic dianhydride as raw materials is not particularly limited, and the properties of the obtained non-thermoplastic polyimide can be controlled not only by controlling the chemical structure of the raw materials but also by controlling the order of addition.

[0050] For the purpose of improving each characteristic of films such as sliding property, thermal conductivity, electrical conductivity, corona resistance, ring rigidity, filler can also be added in the above-mentioned non-thermoplastic polyamic acid. As filler, any filler can be used, as preferred example, silicon dioxide, titanium oxide, aluminum oxide, silicon nitride, boron nitride, calcium hydrogen phosphate, calcium phosphate, mica etc. can be enumerated.

[0051] (Method for producing non-thermoplastic polyimide film)

[0052] In order to obtain the non-thermoplastic polyimide film of the present invention, it is preferred to include the following steps:

[0053] i) a step of reacting an aromatic diamine with an aromatic acid dianhydride in an organic solvent to obtain a polyamic acid solution (hereinafter also referred to as a non-thermoplastic polyamic acid) as a precursor of a non-thermoplastic polyimide;

[0054] ii) a step of casting a film-forming coating material comprising the non-thermoplastic polyamic acid solution from a mold onto a support to form a resin layer (sometimes also referred to as a liquid film);

[0055] iii) a step of heating the resin layer on a support to form a self-supporting gel film, and then peeling the gel film from the support;

[0056] iv) A step of further heating to imidize the remaining amic acid and drying the mixture to obtain a non-thermoplastic polyimide film.

[0057] ii) In the subsequent process, the imidization method is roughly divided into thermal imidization and chemical imidization. The thermal imidization method is a method in which a polyamic acid solution is cast onto a support as a film-forming coating without using a dehydrating ring-closing agent, etc., and imidization is performed only by heating. Another chemical imidization method is a method in which a solution obtained by adding at least one of a dehydrating ring-closing agent and a catalyst as an imidization accelerator to a polyamic acid solution is used as a film-forming coating to promote imidization. Whichever method can be used, the productivity of the chemical imidization method is more excellent.

[0058] As the dehydrating ring-closing agent, an acid anhydride represented by acetic anhydride can be used appropriately. As the catalyst, a tertiary amine such as an aliphatic tertiary amine, an aromatic tertiary amine, or a heterocyclic tertiary amine can be used appropriately.

[0059] As the support body on which the film-forming coating is cast, a glass plate, an aluminum foil, an endless stainless steel belt, a stainless steel drum, etc. can be appropriately used. The heating conditions are set according to the thickness of the film to be finally obtained and the production speed, and after at least one of imidization or drying is partially performed, the polyamic acid film (hereinafter referred to as gel film) is peeled off from the support body to obtain.

[0060] The ends of the gel film are fixed to avoid shrinkage during curing and dried, water, residual solvent and imidization accelerator are removed from the gel film, and the remaining amic acid is completely imidized to obtain a film containing polyimide. The heating conditions can be appropriately set according to the thickness of the final film and the production speed.

[0061] (Thermoplastic polyimide (layer))

[0062] The thermoplastic polyimide contained in the thermoplastic polyimide (layer) in the present invention is obtained by imidizing a polyamic acid which is a precursor thereof.

[0063] The aromatic diamine and aromatic tetracarboxylic dianhydride used in the precursor of the thermoplastic polyimide used in the present invention, that is, the polyamic acid, can be the same as those used in the non-thermoplastic polyimide layer. On the other hand, in order to make a thermoplastic polyimide film, it is preferred to react a diamine with flexibility and an acid dianhydride. As examples of diamines with flexibility, 4,4'-diaminodiphenyl ether, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis(4-aminophenoxyphenyl)propane, etc. can be cited. In order to adjust the glass transition temperature (Tg) of the aforementioned polyimide film, the aforementioned diamine can be used in combination with 1,4-diaminobenzene and / or 4,4'-diamino-2,2'-dimethylbiphenyl. Examples of acid dianhydrides suitable for combination with these diamines include pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, and 4,4'-oxydiphthalic dianhydride.

[0064] For the method for producing the thermoplastic polyamic acid in the present invention, any known method may be used as long as the obtained thermoplastic polyimide satisfies the following requirements. That is, any known method may be used as long as the thermoplastic polyimide obtained by imidizing the obtained polyamic acid has adhesion to metal foil, solder heat resistance, dimensional stability, and flame retardancy required for conventional flexible printed circuit board materials.

[0065] For example, it can be produced by the following steps (Aa) to (Ac):

[0066] (Aa) a step of reacting an aromatic diamine with an aromatic dianhydride in an organic solvent in a state where the aromatic diamine is in excess to obtain a prepolymer having amino groups at both ends;

[0067] (Ab) a step of additionally adding an aromatic diamine having a structure different from that of the aromatic diamine used in step (Aa);

[0068] (Ac) A step of further adding an aromatic acid dianhydride having a structure different from that of the aromatic acid dianhydride used in step (Aa) so that the aromatic diamine and the aromatic acid dianhydride in the step are substantially equimolar and polymerizing.

[0069] Alternatively, the polyamic acid can be obtained by the following steps (Ba) to (Bc):

[0070] (Ba) a step of reacting an aromatic diamine and an aromatic dianhydride in an organic polar solvent in a state where the aromatic dianhydride is in excess to obtain a prepolymer having anhydride groups at both ends;

[0071] (Bb) a step of additionally adding an aromatic acid dianhydride having a structure different from that of the aromatic acid dianhydride used in step (Ba);

[0072] (Bc) A step of further adding an aromatic diamine having a structure different from that of the aromatic diamine used in step (Ba) so that the aromatic diamine and the aromatic acid dianhydride in the entire step are substantially equimolar, and performing polymerization.

[0073] (Solid content concentration of polyamic acid)

[0074] The solid content concentration of the polyamic acid of the present invention is not particularly limited, but is generally 5 to 35 wt%, preferably 10 to 30 wt%. When the concentration is within this range, an appropriate molecular weight and solution viscosity are obtained.

[0075] (Method for producing polyimide adhesive sheet)

[0076] The method for producing a laminate having a thermosetting resin layer and a polyimide layer in the present invention is described in detail. For the method for producing a laminate in the present invention, for example, a non-thermoplastic polyamic acid may be synthesized in the above-mentioned i), and then the above-mentioned ii) to iv) steps may be performed, and thermoplastic polyamic acid may be applied to both sides of a temporarily recovered non-thermoplastic polyimide film, and then imidization may be performed. In addition, a thermoplastic polyimide solution capable of forming a thermoplastic polyimide layer may be applied to both sides of the above-mentioned non-thermoplastic polyimide film and dried to produce a polyimide adhesive sheet.

[0077] As another method, the following method can be cited. In the aforementioned i), while synthesizing non-thermoplastic polyamic acid, the polyamic acid (hereinafter, thermoplastic polyamic acid) as the precursor of thermoplastic polyimide is synthesized in addition. In the aforementioned ii), the coating comprising thermoplastic polyamic acid / film-making coating comprising the above-mentioned non-thermoplastic polyamic acid solution / coating comprising thermoplastic polyamic acid is cast onto a support in a 3-layer mode from a mold, forming a resin layer (sometimes also referred to as liquid film). Carry out iii) and iv) operations in the same manner below, and the polyimide adhesive sheet of the present invention can be made.

[0078] <Flexible Metal-Clad Laminate with Microstrip Line Structure>

[0079] A flexible metal-clad laminate is described, which is characterized in that it has a microstrip line structure, and has a signal line / first polyimide layer / ground layer in sequence, the thickness of the first polyimide layer is 75 to 200 μm and the dielectric loss at 10 GHz is less than 0.008.

[0080] The flexible metal-clad laminate with microstrip line structure of the present invention is as follows Figure 1 As shown, the signal line / first polyimide layer / ground layer are sequentially provided. In addition, a polyimide film having a thickness of 75 to 200 μm and a dielectric loss of 0.008 or less at 10 GHz is used for the first polyimide layer. Thus, the insertion loss at 10 GHz can be set to be greater than -2.4 dB and less than 0 dB.

[0081] In addition, if Figure 2 As shown, there may also be a plurality of signal lines.

[0082] <Method for manufacturing a flexible metal-clad laminate having a microstrip line structure>

[0083] like Figure 3 As shown, multiple polyimide adhesive sheets (polyimide films having a three-layer structure with thermoplastic polyimide layers on both sides of a non-thermoplastic polyimide layer) are sandwiched between two copper foils and bonded together. Then, etching is performed to form a signal line, thereby making it easy to form a microstrip line structure.

[0084] A single-layer thermoplastic polyimide film can be used instead of the aforementioned polyimide adhesive sheet by the following method. That is, for example, overlapping and laminating in the order of copper foil / single-layer thermoplastic polyimide / non-thermoplastic polyimide / single-layer thermoplastic polyimide / non-thermoplastic polyimide / single-layer thermoplastic polyimide / copper foil can also be performed in the same manner. At this time, the total thickness of the thermoplastic polyimide and the non-thermoplastic polyimide (the thickness of the polyimide layer) is preferably 75 μm or more.

[0085] (Thermoplastic polyimide (single layer))

[0086] The thermoplastic polyimide (single layer) is obtained by imidizing the same polyamic acid as the precursor of the thermoplastic polyimide described in the above-mentioned "thermoplastic polyimide (layer)" and making it into a sheet (film). The manufacture of the thermoplastic polyimide (single layer) is preferably carried out by the same method as the manufacturing method of the non-thermoplastic polyimide film.

[0087] (Non-thermoplastic polyimide (single layer))

[0088] The non-thermoplastic polyimide (single layer) is prepared by imidizing the same polyamic acid as the precursor of the non-thermoplastic polyimide and preparing it into a single-layer sheet (film). The non-thermoplastic polyimide (single layer) is preferably prepared by the same method as the method for preparing the non-thermoplastic polyimide film.

[0089] As a lamination method, various known methods can be applied. A hot pressing method obtained by laminating by hot pressing is preferred from the aspect of being able to suppress the generation of wrinkles, etc. of a single-sided flexible metal-clad laminate. As a laminating method for a polyimide adhesive sheet and a metal foil, for example, a hot pressing method using a batch process based on a single plate press, a hot pressing method based on a continuous process using a hot roller laminating device (also referred to as a hot laminating device) or a double belt press (DBP) device can be cited. Among them, from the aspect of productivity and equipment cost including maintenance costs, a hot pressing method using a hot roller laminating device having more than one pair of metal rollers is preferred. The "hot roller laminating device having more than one pair of metal rollers" mentioned here is not particularly limited in its specific device structure as long as it is a device having a metal roller for heating and pressurizing the material.

[0090] The surface roughness (Ra) of the first polyimide layer side of the signal line is preferably small from the perspective of contributing to low transmission loss, and the adhesion must also be guaranteed. Therefore, it is preferably 0.05μm to 0.5μm, more preferably 0.08μm to 0.3μm, and further preferably 0.1μm to 0.2μm. This surface roughness is based on the surface roughness of the polyimide layer side, so it can be controlled by the metal foil used.

[0091] As a method for forming the ground layer, a method of laminating a metal foil will be described. However, one or both of the ground layers may be formed by applying and drying a conductive paste, or may be formed by laminating a conductive shielding film.

[0092] As a lamination method, various known methods can be applied, and a hot pressing method obtained by laminating by hot pressing is preferred from the aspect of being able to suppress the appearance defects of the double-sided flexible metal-clad laminate. As a laminating method, for example, a hot pressing method using a batch process based on a single plate press, a hot pressing method using a continuous process based on a hot roller laminating device (also called a hot laminating device) or a double belt press (DBP) device, etc. can be cited. From the aspect of productivity and equipment cost including maintenance costs, a hot pressing method using a hot roller laminating device having more than one pair of metal rollers is preferred. The "hot roller laminating device having more than one pair of metal rollers" mentioned here is not particularly limited in its specific device structure as long as it is a device having metal rollers for heating and pressurizing the material.

[0093] In this hot pressing method, the metal foil is subjected to two high heat treatments during the manufacture of the single-sided flexible metal-clad laminate and the double-sided flexible metal-clad laminate, so there is a problem that the metal foil is easily caused to have a poor appearance due to heat burning and thermal deformation. In order to improve thermal deformation, in the above-mentioned hot pressing method, a hot pressing method based on a hot roller laminating device with more than one pair of metal rollers is used, and it is appropriate to control the tension of the metal foil and the single-sided flexible metal-clad laminate, or the tension of the metal foil and the double-sided flexible metal-clad laminate. Specifically, it is preferred to set the tension before hot pressing to be higher, and it is preferred to set the lead-out tension of the single-sided flexible metal-clad laminate or the lead-out tension of the double-sided flexible metal-clad laminate to be 40kgf / 270mm or more. In addition, in order to improve heat burning, it is preferred to use a protective film during hot roller lamination.

[0094] The heating method of the laminated material in the above-mentioned heat-pressing means is not particularly limited, and for example, a heating method using a conventionally known method that can heat at a predetermined temperature, such as a heat cycle method, a hot air heating method, an induction heating method, etc., can be used. Similarly, the pressurizing method of the laminated material in the above-mentioned heat-pressing means is not particularly limited, and for example, a pressurizing method using a conventionally known method that can apply a predetermined pressure, such as an oil pressure method, an air pressure method, a gap pressure method, etc., can be used.

[0095] The heating temperature in the above-mentioned hot pressing process, i.e., the pressing temperature (laminating temperature), can be set as long as the temperature of the polyimide adhesive sheet on the side that is in close contact with the metal foil during the manufacture of the single-sided flexible metal-clad laminate is the minimum temperature that can be in close contact with the metal foil. In addition, it can be set as long as the polyimide adhesive sheet on the side that is not in close contact with the metal foil is not attached to other materials, peripheral components, etc. Therefore, the laminating temperature during the manufacture of the single-sided flexible metal-clad laminate can be set to the glass transition temperature (Tg) of the polyimide adhesive sheet used + 20°C to (Tg) + 60°C.

[0096] It should be noted that, when the polyimide adhesive sheet is heated at a temperature exceeding Tg, as the heating temperature becomes higher, the polyimide adhesive sheet softens and becomes easy to bond with the surrounding components. At this time, the polyimide adhesive sheet on the side that is not closely attached to the metal foil is likely to contact with the surrounding components during processing, so the preferred adhesion is relatively low. Therefore, the above-mentioned lamination temperature is preferably adopted.

[0097] On the other hand, when manufacturing a double-sided flexible metal-clad laminate, it is desirable that all layers have high adhesion. Therefore, lamination can be performed at a higher temperature than a single-sided flexible metal-clad laminate. Therefore, the lamination temperature when manufacturing a double-sided flexible metal-clad laminate is preferably a temperature of the glass transition temperature (Tg)+20°C to (Tg)+90°C of the polyimide adhesive sheet used, and more preferably Tg+50°C to (Tg)+80°C of the adhesive sheet (C).

[0098] The lamination speed in the thermocompression bonding step is preferably 0.5 m / min or more, more preferably 1.0 m / min or more. At 0.5 m / min or more, sufficient thermocompression bonding can be achieved, and at 1.0 m / min or more, productivity can be further improved.

[0099] There is an advantage that the higher the pressure in the above-mentioned hot pressing process, that is, the higher the lamination pressure, the lower the lamination temperature and the faster the lamination speed. However, if the lamination pressure is usually too high, there is a tendency for the dimensional change of the obtained metal-clad laminate to deteriorate. In addition, on the contrary, the lower the lamination pressure, the lower the bonding strength of the metal foil of the obtained metal-clad laminate. Therefore, the lamination pressure is preferably within the range of 49N / cm to 490N / cm (5kgf / cm to 50kgf / cm), and more preferably within the range of 98N / cm to 294N / cm (10kgf / cm to 30kgf / cm). When it is within this range, the three conditions of lamination temperature, lamination speed and lamination pressure can be made good, which can further improve productivity.

[0100] In order to obtain the single-sided flexible metal-clad laminate or double-sided flexible metal-clad laminate of the present invention, it is preferred to use a hot roller laminating device that continuously heats and presses the laminated materials. In the hot roller laminating device, a laminated material outlet means for outlet of the laminated material may be provided at the front section of the hot laminating means, and a laminated material winding means for winding up the laminated material may be provided at the rear section of the hot laminating means. By providing these means, the productivity of the hot roller laminating device can be further improved. The specific structure of the laminated material outlet means and the laminated material winding means is not particularly limited, and for example, a known roller-shaped winder that can wind up the adhesive sheet, metal foil, or the obtained metal-clad laminate can be cited.

[0101] It would be more preferable if winding means and exporting means for winding or exporting the protective film are further provided. If these winding means / exporting means are provided, the protective film can be reused by winding up the protective film temporarily used in the hot pressing process and setting it again on the exporting side. In addition, when the protective film is wound up, in order to align its two ends, end position detection means and winding position correction means can be provided. In this way, the ends can be aligned and wound up with good precision, so the efficiency of reuse can be improved. It should be noted that the specific composition of these winding means, exporting means, end position detection means and winding position correction means is not particularly limited, and various devices known in the past can be used.

[0102] (metal foil)

[0103] The metal foil that can be used in the present invention is not particularly limited. When the flexible metal-clad laminate of the present invention is used in electronic equipment / electrical equipment applications, for example, foils formed of copper or copper alloys, stainless steel or its alloys, nickel or nickel alloys (including 42 alloys), aluminum or aluminum alloys can be cited. In common flexible laminates, copper foils such as rolled copper foil and electrolytic copper foil are mostly used, which can also be preferably used in the present invention. It should be noted that a rust-proof layer, a heat-resistant layer or an adhesive layer can be coated on the surface of these metal foils. In addition, the thickness of the above-mentioned metal foil is not particularly limited, as long as it is a thickness that meets its purpose and can fully function.

[0104] Transmission loss is mainly composed of conductor loss caused by copper foil and dielectric loss caused by insulating resin substrate. Conductor loss is affected by the skin effect of copper foil, which becomes more prominent at higher frequencies. Therefore, in order to suppress transmission loss in high-frequency applications, copper foil with low roughness is required. In addition, it is known that the conductivity of alloys containing magnetic materials such as nickel and cobalt used for rust prevention and improved adhesion changes depending on the frequency, which may lead to worsening transmission loss. Therefore, care must be taken when using.

[0105] The thickness of the metal foil is preferably 3 μm to 30 μm, more preferably 5 μm to 20 μm. The surface roughness (Ra) of the metal foil is preferably 0.05 μm to 0.5 μm, more preferably 0.08 μm to 0.3 μm, and further preferably 0.1 μm to 0.2 μm, if the adhesion with the polyimide layer is taken into consideration. When the surface roughness (Ra) is smaller than this range, the adhesion with the polyimide layer decreases, and when Ra is larger than this range, the conductor loss increases, so it is difficult to reduce the transmission loss.

[0106] <Surface Treatment of Polyimide Adhesive Sheet>

[0107] The polyimide adhesive sheet has an adhesive layer in the outermost layer, so it is not necessary to implement a general surface treatment that improves the adhesion. However, when the adhesive sheets are laminated to each other, since they are the same material, the surface state is the same state, and there is a tendency that the anchoring effect is small and the adhesion is low. In this case, the adhesion of the polyimide adhesive sheets can be improved by implementing a surface treatment of the adhesive layer that is usually not implemented on the single side of at least the laminating surface.

[0108] The surface treatment method is not particularly limited, and for example, corona treatment, plasma treatment, sandblasting, etc. can be used.

[0109] <Flexible Metal-Clad Laminate with Stripline Structure>

[0110] A flexible metal-clad laminate having a stripline structure and including at least a ground layer / a second polyimide layer / an adhesive layer / a signal line / a first polyimide layer / a ground layer in this order will be described.

[0111] The flexible metal-clad laminate with a strip line structure of the present invention is as follows Figure 4 As shown, the first polyimide layer / second polyimide layer / adhesive layer (adhesive layer 1) / signal line / first polyimide layer / ground layer are sequentially provided. In addition, the first polyimide layer and the second polyimide layer each use a polyimide film having a thickness of 75 to 200 μm and a dielectric loss of 0.008 or less at 10 GHz. Thus, the insertion loss at 10 GHz can be set to be greater than -3.2 dB and less than 0 dB.

[0112] In addition, you can Figure 5 As shown, an adhesive layer (adhesive layer 2) is provided between the copper layer serving as the signal line and the first polyimide layer.

[0113] Furthermore, it can also be Figure 6 As shown, there are multiple signal lines.

[0114] The flexible metal-clad laminate with a strip line structure of the present invention is as follows Figure 7 As shown, a single-sided flexible metal-clad laminate (ground layer / second polyimide layer) can be manufactured by laminating a single-sided flexible metal-clad laminate (ground layer / second polyimide layer) with an adhesive layer (joining sheet) and a double-sided flexible metal-clad laminate. An example of using a joining sheet in the adhesive layer is described here. On the other hand, a flexible metal-clad laminate can be similarly manufactured by applying an adhesive to the polyimide surface of a single-sided flexible metal-clad laminate or the polyimide surface of a double-sided flexible metal-clad laminate instead of the joining sheet and laminating.

[0115] <Method for manufacturing single-sided flexible metal-clad laminate>

[0116] In the present invention, the single-sided flexible metal-clad laminate is obtained by laminating a metal foil (ground layer) on a thermoplastic polyimide layer as an adhesive layer of the aforementioned polyimide adhesive sheet (a polyimide film having a three-layer structure with thermoplastic polyimide layers on both sides of a non-thermoplastic polyimide layer). Figure 8 As shown in FIG. 1 , multiple polyimide adhesive sheets with a thickness of less than 75 μm are laminated (stacked) to form an adhesive layer with a thickness of more than 75 μm, and then laminated to a metal layer on one side to form a single-sided flexible metal-clad laminate. Fig. 9 As shown, a single-sided flexible metal-clad laminate is produced by laminating a metal foil and a plurality of polyimide adhesive sheets together.

[0117] Fig. 9In the example of using a polyimide adhesive sheet (a polyimide film having a three-layer structure with thermoplastic polyimide layers on both sides of a non-thermoplastic polyimide layer), it is also possible to Fig.10 Thus, the metal foil (ground layer) / thermoplastic polyimide (single layer) / non-thermoplastic polyimide (single layer) are bonded in this order. At this time, the total thickness of the thermoplastic polyimide and the non-thermoplastic polyimide is preferably 75 μm or more.

[0118] (Thermoplastic polyimide (single layer))

[0119] The thermoplastic polyimide (single layer) is the same as the thermoplastic polyimide (single layer) in the flexible metal-clad laminate with a microstrip line structure of the present invention (hereinafter referred to as "flexible metal-clad laminate 1"). That is, the polyamic acid identical to the polyamic acid as a precursor of the thermoplastic polyimide described in the above-mentioned "thermoplastic polyimide (layer)" is imidized and made into a sheet (film). The manufacture of the thermoplastic polyimide (single layer) is preferably carried out by the same method as the manufacturing method of the non-thermoplastic polyimide film.

[0120] (Non-thermoplastic polyimide (single layer))

[0121] The non-thermoplastic polyimide (single layer) is the same as the non-thermoplastic polyimide (single layer) in the flexible metal-clad laminate 1. That is, the non-thermoplastic polyimide (single layer) is imidized with the same polyamic acid as the precursor of the non-thermoplastic polyimide and made into a single-layer sheet (film). The manufacture of the non-thermoplastic polyimide (single layer) is preferably carried out by the same method as the manufacturing method of the non-thermoplastic polyimide film.

[0122] In addition, you can Fig.11 As shown, the layers of (thermoplastic polyimide / non-thermoplastic polyimide) are laminated in the order of metal foil (ground layer) / thermoplastic polyimide / non-thermoplastic polyimide / thermoplastic polyimide so that the layers are repeated multiple times. The total thickness of the thermoplastic polyimide and the non-thermoplastic polyimide is 75 μm or more.

[0123] As the lamination method, various known methods can be applied, and the same method as the lamination method in the method for producing the flexible metal-clad laminate 1 described above can be adopted.

[0124] <Method for manufacturing double-sided flexible metal-clad laminate>

[0125] In the present invention, the double-sided flexible metal-clad laminate can be obtained by laminating a metal foil on the thermoplastic polyimide layer as an adhesive layer of the aforementioned polyimide adhesive sheet (a polyimide film having a three-layer structure with thermoplastic polyimide layers on both sides of a non-thermoplastic polyimide layer). Fig.12 As shown, metal foil / multiple polyimide adhesive sheets / metal foil are stacked together to make a double-sided flexible metal-clad laminate ( Fig.12 b). Alternatively, a plurality of polyimide adhesive sheets may be replaced by using Fig.13 The polyimide adhesive sheet shown is formed by laminating (stacking) a plurality of polyimide adhesive sheets having a thickness of less than 75 μm. Next, a double-sided flexible metal-clad laminate ( Fig.12 b. Fig.13 b) is etched on one side, thereby forming a signal line. The signal line can be Figure 6 As shown in FIG. 1 , there are multiple. As described above, it is possible to produce a double-sided flexible metal-clad laminate ( Fig.12 c. Fig.13 c).

[0126] The surface roughness (Ra) of the first polyimide layer side of the signal line is preferably small in terms of helping to reduce transmission loss. However, since adhesion also needs to be guaranteed, it is preferably 0.05 μm to 0.5 μm, more preferably 0.08 μm to 0.3 μm, and further preferably 0.1 μm to 0.2 μm. This surface roughness is based on the surface roughness of the first polyimide layer side of the metal foil stacked on the double-sided flexible metal-clad laminate, so it can be controlled by the metal foil used.

[0127] As a method for forming the ground layer, the method of laminating a metal foil has been described, but the same method as the method for forming the ground layer in the method for manufacturing the flexible metal-clad laminate 1 can also be adopted. That is, one or both of the ground layers can be formed by applying and drying a conductive paste, or by laminating a conductive shielding film.

[0128] As the lamination method, various known methods can be applied, and the same method as the lamination method in the method for producing the flexible metal-clad laminate 1 described above can be adopted.

[0129] (metal foil)

[0130] The metal foil that can be used in the flexible metal-clad laminate having a strip line structure of the present invention is not particularly limited, and the same metal foil as that in the flexible metal-clad laminate 1 can be used.

[0131] <Surface Treatment of Polyimide Adhesive Sheet>

[0132] The polyimide adhesive sheet in the flexible metal-clad laminate with a wire structure is similar to the polyimide adhesive sheet in the above-mentioned flexible metal-clad laminate 1, and has an adhesive layer in the outermost layer. Therefore, it is not necessary to implement a general surface treatment that improves adhesion. However, when the adhesive sheets are laminated to each other, since they are the same material each other, the surface state is the same state, and there is a tendency that the anchoring effect is small and the adhesion is low. In this case, by implementing the surface treatment of the adhesive layer that is usually not implemented to the single-sided implementation of at least the laminating surface, the adhesion of the polyimide adhesive sheets can be improved.

[0133] The surface treatment method is not particularly limited, and for example, corona treatment, plasma treatment, sandblasting, etc. can be used.

[0134] The present invention may include the following inventions.

[0135] (A1) A multi-layer flexible metal-clad laminate, characterized in that it is a flexible metal-clad laminate with a microstrip line structure, wherein the flexible metal-clad laminate has at least a signal line / polyimide layer / ground layer in sequence, the thickness of the polyimide layer is 75 to 200 μm and the dielectric loss at 10 GHz is less than 0.008.

[0136] (A2) The flexible metal-clad laminate according to (A1), wherein the insertion loss at 10 GHz is not less than -2.4 dB and not more than 0 dB.

[0137] (A3) The flexible metal-clad laminate according to (A1) or (A2), wherein the polyimide layer includes a thermoplastic polyimide layer and a non-thermoplastic polyimide layer.

[0138] (A4) The flexible metal-clad laminate according to any one of (A1) to (A3), wherein the polyimide layer has a three-layer structure including thermoplastic polyimide layers on both sides of a non-thermoplastic polyimide layer.

[0139] (A5) The flexible metal-clad laminate according to (A4), wherein the polyimide layer is a laminate of two or more polyimide films having the three-layer structure and having a thickness of less than 75 μm.

[0140] (A6) The flexible metal-clad laminate according to any one of (A1) to (A5), further comprising two or more signal lines.

[0141] (A7) The flexible metal-clad laminate according to any one of (A1) to (A6), wherein the surface roughness (Ra) of the polyimide layer side of the signal line is 0.05 μm to 0.5 μm.

[0142] (A8) A method for manufacturing a flexible metal-clad laminate, characterized in that the flexible metal-clad laminate has a microstrip line structure, the multi-layer flexible metal-clad laminate has at least a signal line / polyimide layer / ground layer in sequence, the polyimide layer uses a polyimide film with a thickness of 75 to 200 μm and a dielectric loss of less than 0.008 at 10 GHz.

[0143] (A9) The method for producing a flexible metal-clad laminate according to (A8), wherein the insertion loss of the flexible metal-clad laminate at 10 GHz is greater than or equal to -2.4 dB and less than or equal to 0 dB.

[0144] (A10) The method for producing a flexible metal-clad laminate according to (A8) or (A9), wherein the polyimide layer comprises a thermoplastic polyimide layer and a non-thermoplastic polyimide.

[0145] (A11) The method for producing a flexible metal-clad laminate according to any one of (A8) to (A10), wherein the polyimide layer is formed by laminating a thermoplastic polyimide film and a non-thermoplastic polyimide.

[0146] (A12) The method for producing a flexible metal-clad laminate according to any one of (A8) to (A11), wherein the polyimide layer has a three-layer structure having thermoplastic polyimide layers on both sides of a non-thermoplastic polyimide layer.

[0147] (A13) The method for producing a flexible metal-clad laminate according to (A12), wherein the polyimide layer is formed by laminating at least two polyimide films having a thickness of less than 75 μm and having the three-layer structure.

[0148] (A14) The method for producing a flexible metal-clad laminate according to any one of (A8) to (A13), wherein the flexible metal-clad laminate has two or more signal lines.

[0149] (A15) The method for producing a flexible metal-clad laminate according to any one of (A8) to (A14), wherein the surface roughness (Ra) of the polyimide layer side of the signal line is 0.05 μm to 0.5 μm.

[0150] (B1) A multi-layer flexible metal-clad laminate, characterized in that it has a strip line structure, wherein the multi-layer flexible metal-clad laminate has at least a ground layer / a first polyimide layer / an adhesive layer / a signal line / a second polyimide layer / a ground layer in sequence, wherein the thickness of the first polyimide layer and the second polyimide layer is 75 to 200 μm and the dielectric loss at 10 Hz is less than 0.008.

[0151] (B2) The multi-layer flexible metal-clad laminate according to (B1), wherein the insertion loss at 10 GHz is greater than or equal to -3.2 dB and less than or equal to 0 dB.

[0152] (B3) The multilayer flexible metal-clad laminate according to (B1) or (B2), wherein the first polyimide layer and the second polyimide layer include a thermoplastic polyimide layer and a non-thermoplastic polyimide layer.

[0153] (B4) The multilayer flexible metal-clad laminate according to any one of (B1) to (B3), characterized in that the first polyimide layer and the second polyimide layer have a three-layer structure having thermoplastic polyimide layers on both sides of non-thermoplastic polyimide.

[0154] (B5) The multilayer flexible metal-clad laminate according to (B4), characterized in that the first polyimide layer and the second polyimide layer are laminated products of two or more polyimide films having the three-layer structure and a thickness of less than 75 μm.

[0155] (B6) The multilayer flexible metal-clad laminate according to any one of (B1) to (B5), further comprising an adhesive layer between the copper layer serving as the signal line and the second polyimide layer.

[0156] (B7) The multilayer flexible metal-clad laminate according to any one of (B1) to (B6), characterized in having two or more signal lines.

[0157] (B8) The multilayer flexible metal-clad laminate according to any one of (B1) to (B7), wherein the surface roughness (Ra) of the second polyimide layer side of the signal line is 0.05 μm to 0.5 μm.

[0158] (B9) A method for manufacturing a multi-layer flexible metal-clad laminate, characterized in that the multi-layer flexible metal-clad laminate has a strip line structure, and the multi-layer flexible metal-clad laminate has at least a ground layer / a first polyimide layer / an adhesive layer / a signal line / a second polyimide layer / a ground layer in sequence, and the first polyimide layer and the second polyimide layer use a polyimide film with a thickness of 75 to 200 μm and a dielectric loss of less than 0.008 at 10 Hz.

[0159] (B10) The method for manufacturing a multi-layer flexible metal-clad laminate according to (B9), wherein the insertion loss of the multi-layer flexible metal-clad laminate at 10 GHz is greater than -3.2 dB and less than 0 dB.

[0160] (B11) The method for producing a multilayer flexible metal-clad laminate according to (B9) or (B10), wherein the first polyimide layer and the second polyimide layer comprise a thermoplastic polyimide layer and a non-thermoplastic polyimide.

[0161] (B12) A method for manufacturing a multilayer flexible metal-clad laminate according to any one of (B9) to (B11), characterized in that the first polyimide layer and the second polyimide layer are laminated by bonding a thermoplastic polyimide film and a non-thermoplastic polyimide.

[0162] (B13) A method for manufacturing a multilayer flexible metal-clad laminate according to any one of (B9) to (B12), characterized in that the first polyimide layer and the second polyimide layer have a three-layer structure having thermoplastic polyimide layers on both sides of a non-thermoplastic polyimide.

[0163] (B14) A method for manufacturing a multilayer flexible metal-clad laminate according to (B13), characterized in that the first polyimide layer and the second polyimide layer are formed by laminating at least two or more polyimide films having the three-layer structure and a thickness of less than 75 μm.

[0164] (B15) The method for producing a multilayer flexible metal-clad laminate according to any one of (B9) to (B14), further comprising an adhesive layer between the copper layer serving as the signal line and the second polyimide layer.

[0165] (B16) The method for manufacturing a multilayer flexible metal-clad laminate according to any one of (B9) to (B15), wherein the multilayer flexible metal-clad laminate has two or more signal lines.

[0166] (B17) The method for manufacturing a multilayer flexible metal-clad laminate according to any one of (B9) to (B16), characterized in that the surface roughness (Ra) of the second polyimide layer side of the aforementioned signal line is 0.05 μm to 0.5 μm.

[0167] (C1) A flexible metal-clad laminate, characterized in that it has a microstrip line structure, wherein the flexible metal-clad laminate has at least a signal line / a first polyimide layer / a ground layer in sequence, the thickness of the first polyimide layer is 75 to 200 μm and the dielectric loss at 10 GHz is less than 0.008.

[0168] (C2) The flexible metal-clad laminate according to (C1), further comprising a ground layer / a second polyimide layer / an adhesive layer, wherein the flexible metal-clad laminate comprises at least a ground layer / a second polyimide layer / an adhesive layer / a signal line / a first polyimide layer / a ground layer in this order,

[0169] The second polyimide layer has a thickness of 75 to 200 μm and a dielectric loss of 0.008 or less at 10 GHz.

[0170] (C3) The flexible metal-clad laminate according to (C1) or (C2), wherein the insertion loss at 10 GHz is greater than or equal to -3.2 dB and less than or equal to 0 dB.

[0171] (C4) A flexible metal-clad laminate according to any one of (C1) to (C3), characterized in that the first polyimide layer has a thermoplastic polyimide layer and a non-thermoplastic polyimide layer, or the first polyimide layer and the second polyimide layer each have a thermoplastic polyimide layer and a non-thermoplastic polyimide layer.

[0172] (C5) A flexible metal-clad laminate according to any one of (C1) to (C4), characterized in that the first polyimide layer has a three-layer structure having thermoplastic polyimide layers on both sides of a non-thermoplastic polyimide layer, or the first polyimide layer and the second polyimide layer each have a three-layer structure having thermoplastic polyimide layers on both sides of a non-thermoplastic polyimide layer.

[0173] (C6) The flexible metal-clad laminate according to (C5), characterized in that the first polyimide layer is a stack of two or more polyimide films having the three-layer structure and a thickness of less than 75 μm, or the first polyimide layer and the second polyimide layer are each a stack of two or more polyimide films having the three-layer structure and a thickness of less than 75 μm.

[0174] (C7) The flexible metal-clad laminate according to any one of (C1) to (C6), wherein the signal line is a copper layer.

[0175] An adhesive layer is further provided between the copper layer and the first polyimide layer.

[0176] (C8) The flexible metal-clad laminate according to any one of (C1) to (C7), further comprising two or more signal lines.

[0177] (C9) The flexible metal-clad laminate according to any one of (C1) to (C8), wherein the surface roughness (Ra) of the signal line on the first polyimide layer side is 0.05 μm to 0.5 μm.

[0178] (C10) A method for manufacturing a flexible metal-clad laminate, characterized in that the flexible metal-clad laminate has a microstrip line structure, and the flexible metal-clad laminate has at least a signal line / a first polyimide layer / a ground layer in sequence, and as the first polyimide layer, a polyimide film with a thickness of 75 to 200 μm and a dielectric loss of less than 0.008 at 10 GHz is used.

[0179] (C11) The method for manufacturing a flexible metal-clad laminate according to (C10), further comprising a ground layer / a second polyimide layer / an adhesive layer, wherein the flexible metal-clad laminate comprises at least a ground layer / a second polyimide layer / an adhesive layer / a signal line / a second polyimide layer / a ground layer in this order,

[0180] As the second polyimide layer, a polyimide film having a thickness of 75 to 200 μm and a dielectric loss of 0.008 or less at 10 GHz is used.

[0181] (C12) The method for manufacturing a flexible metal-clad laminate according to (C10) or (C11), wherein the insertion loss of the flexible metal-clad laminate at 10 GHz is greater than or equal to -3.2 dB and less than or equal to 0 dB.

[0182] (C13) A method for manufacturing a flexible metal-clad laminate according to any one of (C10) to (C12), characterized in that the first polyimide layer has a thermoplastic polyimide layer and a non-thermoplastic polyimide layer, or the first polyimide layer and the second polyimide layer each have a thermoplastic polyimide layer and a non-thermoplastic polyimide layer.

[0183] (C14) A method for manufacturing a flexible metal-clad laminate according to any one of (C10) to (C13), characterized in that a thermoplastic polyimide film and a non-thermoplastic polyimide are bonded together to form the aforementioned first polyimide layer, or a thermoplastic polyimide film and a non-thermoplastic polyimide are bonded together to form the aforementioned first polyimide layer and the aforementioned second polyimide layer, respectively.

[0184] (C15) A method for manufacturing a flexible metal-clad laminate according to any one of (C10) to (C14), characterized in that the first polyimide layer has a three-layer structure having thermoplastic polyimide layers on both sides of a non-thermoplastic polyimide layer, or the first polyimide layer and the second polyimide layer each have a three-layer structure having thermoplastic polyimide layers on both sides of a non-thermoplastic polyimide layer.

[0185] (C16) The method for manufacturing a flexible metal-clad laminate according to (C15), characterized in that the first polyimide layer is formed by laminating at least two or more polyimide films having the three-layer structure and a thickness of less than 75 μm, or the first polyimide layer and the second polyimide layer are each formed by laminating at least two or more polyimide films having the three-layer structure and a thickness of less than 75 μm.

[0186] (C17) The method for producing a flexible metal-clad laminate according to any one of (C10) to (C16), wherein the signal line is a copper layer.

[0187] An adhesive layer is further provided between the copper layer and the first polyimide layer.

[0188] (C18) The method for producing a flexible metal-clad laminate according to any one of (C10) to (C17), wherein the flexible metal-clad laminate comprises two or more signal lines.

[0189] (C19) The method for producing a flexible metal-clad laminate according to any one of (C10) to (C18), wherein the surface roughness (Ra) of the signal line on the first polyimide layer side is 0.05 μm to 0.5 μm.

[0190] Example

[0191] The present invention is specifically described below by way of examples, but the present invention is not limited to these examples. It should be noted that the dielectric constant of the polyimide film in the synthesis examples, examples and comparative examples, the dielectric loss tangent, the measurement of the transmission characteristics of the FPC, the peel strength, the thickness of the film, and the evaluation method of the surface roughness of the copper foil are as follows.

[0192] (Determination of dielectric constant and dielectric loss tangent)

[0193] A cavity resonator perturbation method complex dielectric constant evaluation device (manufactured by Kanto Electronics Application Development Co., Ltd.) was used as a measuring device to measure the dielectric constant and dielectric loss tangent of the multilayer polyimide film at the following frequency.

[0194] Measurement frequency: 10 GHz

[0195] Measurement conditions: temperature 22℃~24℃, humidity 45%~55%

[0196] Measurement sample: A sample left to stand for 24 hours under the above-mentioned measurement conditions was used.

[0197] (Manufacturing of FCCL, measurement of transmission characteristics of microstrip lines and strip lines)

[0198] A polyimide film and a copper foil were laminated under the following conditions to obtain a double-sided FCCL.

[0199] Copper foil used: thickness 12 μm, roughness of the surface bonded to the polyimide film is 0.45 μm or less

[0200] Lamination conditions of polyimide and copper foil: lamination temperature 360°C, lamination pressure 0.8 tons, lamination speed 1m / min

[0201] In the production of the microstrip line circuit, one side of the double-sided FCCL is etched to produce a microstrip line with a line length of 10 cm, and the circuit part and the terminal part are copper plated. The circuit width is calculated based on the thickness, dielectric constant, and dielectric loss tangent of the constituent materials so that the characteristic impedance becomes 50Ω.

[0202] Then, the microstrip line circuit was laminated by heating under reduced pressure at 160°C for 30 minutes with the aid of a single-sided FCCL and an adhesive layer (bonding sheet) to produce an FPC test piece having a stripline structure. The circuit width was calculated based on the thickness, dielectric constant, and dielectric loss tangent of the constituent materials so that the characteristic impedance became 50Ω.

[0203] The obtained flexible metal-clad laminate with microstrip line circuit and flexible metal-clad laminate with strip line circuit were subjected to the following treatments. That is, after drying at 150°C for 30 minutes, humidity was adjusted for more than 24 hours in a test room adjusted to 23°C and 55% RH. Then, the insertion loss S21 parameter was measured using a network analyzer E5071C (Keysight Technologies) and a GSG250 probe to obtain the transmission loss (dB / 100mm) at a measurement frequency of 10 GHz.

[0204] (Determination method of peel strength)

[0205] FCCL was analyzed according to "6.5 Peel Strength" of JIS C6471. Specifically, a 1 mm wide metal foil portion was peeled off at a peeling angle of 90 degrees and 100 mm / min, and the load was measured. For peel strength, a value of "○" (good) was given for a value of 12 N / cm or more, and a value of "×" (poor) was given for a value of less than 12 N / cm.

[0206] (Thickness of film)

[0207] The thickness of the film was measured using a contact thickness gauge "LASER HOLOGAGE" manufactured by Mitsutoyo Co., Ltd.

[0208] (Surface roughness Ra of copper foil)

[0209] The arithmetic mean roughness was measured under the following conditions using a light wave interferometer surface roughness meter (NewView5030 system manufactured by ZYGO Corporation).

[0210] (Measurement conditions)

[0211] Objective lens: 50x Mirror zoom: 2

[0212] FDA Res:Normal

[0213] Analysis conditions:

[0214] Remove: Cylinder

[0215] Filter: High Pass

[0216] Filter Low Waven: 0.002mm

[0217] (Synthesis example 1)

[0218] While maintaining the reaction system at 20°C, 11.64 kg of 1,3-bis(4-aminophenoxy)benzene (hereinafter also referred to as TPE-R) and 11.28 kg of 4,4'-diamino-2,2'-dimethylbiphenyl (hereinafter also referred to as m-TB) were added to 328.79 kg of N,N-dimethylformamide (hereinafter also referred to as DMF), and stirred under a nitrogen atmosphere. After visually confirming that TPE-R and m-TB were dissolved, 14.66 kg of 3,3',4,4'-biphenyltetracarboxylic dianhydride (hereinafter also referred to as BPDA) and 7.39 kg of pyromellitic anhydride (hereinafter also referred to as PMDA) were added, and stirred for 30 minutes. Next, 4.31 kg of p-phenylenediamine (hereinafter also referred to as PDA) and 9.85 kg of PMDA were added, and stirred for 30 minutes.

[0219] Finally, a solution was prepared by dissolving 0.9 kg of PMDA in DMF to a solid content concentration of 7%. This solution was gradually added to the reaction solution while noting the increase in viscosity. The polymerization was terminated when the viscosity reached 3000 poise.

[0220] In the polyamic acid solution, an imidization accelerator formed by acetic anhydride / isoquinoline / DMF (weight ratio 2.0 / 0.7 / 4.0) was added to the polyamic acid solution at a weight ratio of 50%, and the mixture was continuously stirred with a mixer, extruded from a T-die and cast onto a stainless steel endless belt. The resin film was heated at 130°C for 100 seconds, and the self-supporting gel film was peeled off from the endless belt and fixed to a tenter clip, and dried and imidized at 250°C for 17 seconds, 350°C for 17 seconds, and 400°C for 120 seconds to obtain a polyimide film with a thickness of 17 μm.

[0221] (Synthesis example 2)

[0222] While the reaction system was kept at 20°C, 15.76 kg of 4,4'-diaminodiphenyl ether (hereinafter also referred to as ODA) was added to 328.94 kg of DMF, and stirred under a nitrogen atmosphere. After visually confirming that ODA was dissolved, 17.37 kg of BPDA and 2.57 kg of PMDA were added, and stirred for 30 minutes. Next, 11.14 kg of m-TB and 12.30 kg of PMDA were added, and stirred for 30 minutes.

[0223] Finally, a solution was prepared by dissolving 0.9 kg of PMDA in DMF to a solid content concentration of 7%. This solution was gradually added to the reaction solution while noting the increase in viscosity. The polymerization was terminated when the viscosity reached 3000 poise.

[0224] In the polyamic acid solution, an imidization accelerator formed by acetic anhydride / isoquinoline / DMF (weight ratio 2.0 / 0.7 / 4.0) was added to the polyamic acid solution at a weight ratio of 50%, and the mixture was continuously stirred with a mixer, extruded from a T-die and cast onto a stainless steel endless belt. The resin film was heated at 130°C for 100 seconds, and the self-supporting gel film was peeled off from the endless belt and fixed to a tenter clip, and dried and imidized at 250°C for 17 seconds, 350°C for 17 seconds, and 400°C for 120 seconds to obtain a polyimide film with a thickness of 17 μm.

[0225] (Synthesis example 3)

[0226] While maintaining the reaction system at 20°C, 10.53 kg of ODA and 32.39 kg of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (hereinafter, also referred to as BAPP) were added to 657.82 kg of DMF, and stirred under a nitrogen atmosphere. After visually confirming that ODA and BAPP were dissolved, 16.95 kg of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (hereinafter, also referred to as BTDA) and 14.34 kg of PMDA were added, and stirred for 30 minutes. Next, 14.22 kg of PDA and 29.83 kg of PMDA were added, and stirred for 30 minutes.

[0227] Finally, a solution was prepared by dissolving 1.7 kg of PDA in DMF to a solid content concentration of 10%. This solution was gradually added to the reaction solution while noting the increase in viscosity. The polymerization was terminated when the viscosity reached 3000 poise.

[0228] In the polyamic acid solution, an imidization accelerator formed by acetic anhydride / isoquinoline / DMF (weight ratio 2.0 / 0.7 / 4.0) was added to the polyamic acid solution at a weight ratio of 50%, and the mixture was continuously stirred with a mixer, extruded from a T-die and cast onto a stainless steel endless belt. The resin film was heated at 130°C for 100 seconds, and the self-supporting gel film was peeled off from the endless belt and fixed to a tenter clip, and dried and imidized at 250°C for 17 seconds, 350°C for 17 seconds, and 400°C for 120 seconds to obtain a polyimide film with a thickness of 17 μm.

[0229] (Synthesis of Thermoplastic Polyimide Precursor (Polyamic Acid))

[0230] 29.8 g of BAPP was dissolved in 249 g of DMF cooled to 10°C. 21.4 g of BPDA was added thereto and dissolved, and then stirred for 30 minutes to form a prepolymer. A separately prepared DMF solution of BAPP (1.57 g of BAPP / 31.4 g of DMF) was then carefully added to the solution, and the addition was stopped when the viscosity reached about 1000 poise. The mixture was stirred for 1 hour to obtain a polyamic acid solution having a solid content concentration of about 17% by weight and a rotational viscosity of 1000 poise at 23°C.

[0231] <Flexible Metal-Clad Laminate with Microstrip Line Structure>

[0232] (Example 1)

[0233] After the thermoplastic polyamic acid solution was diluted with DMF to a solid content concentration of 10% by weight, the polyamic acid was applied to one side of the film obtained in Synthesis Example 1 using a comma coater so that the final single-side thickness was 4 μm, and heated in a drying oven set at 140° C. for 1 minute. The other side was also coated with polyamic acid in a manner such that the final thickness was 4 μm, and then heated in a drying oven set at 140° C. for 1 minute. Then, heat treatment was performed in a far-infrared heating oven at an atmosphere temperature of 360° C. for 20 seconds to obtain a polyimide laminate with a total thickness of 25.0 μm. Furthermore, the copper foil / 3 polyimide laminates with a total thickness of 25.0 μm / copper foil were stacked in the order of copper foil / 3 polyimide laminates with a total thickness of 25.0 μm / copper foil, and heat laminated using a hot roll laminator at a lamination temperature of 360° C., a lamination pressure of 0.8 tons, and a lamination speed of 1.0 m / min to produce a double-sided copper clad laminate (double-sided FCCL) (copper foil: CF-T49A-HD2, Ra=0.15 μm, thickness of polyimide layer: 75 μm). The aforementioned 3 polyimide laminates correspond to the aforementioned "first polyimide layer".

[0234] A microstrip line with a line length of 10 cm was produced by etching one side of a double-sided FCCL including a polyimide layer, and copper plating was performed on the circuit part and the terminal part to produce a test piece of a flexible metal-clad laminate of a microstrip line. The circuit width was calculated from the thickness, dielectric constant, and dielectric loss tangent of the constituent materials so that the characteristic impedance became 50Ω.

[0235] (Example 2)

[0236] A test piece of a flexible metal-clad laminate was prepared in the same manner as in Example 1 except that four polyimide laminates having a total thickness of 25.0 μm obtained in Example 1 were stacked. The four polyimide laminates correspond to the “first polyimide layer”.

[0237] (Example 3)

[0238] A test piece of a flexible metal-clad laminate was prepared in the same manner as in Example 1 except that six polyimide laminates having a total thickness of 25.0 μm obtained in Example 1 were stacked. The six polyimide laminates correspond to the “first polyimide layer”.

[0239] (Example 4)

[0240] A test piece of a flexible metal-clad laminate was prepared in the same manner as in Example 1 except that eight polyimide laminates having a total thickness of 25.0 μm obtained in Example 1 were stacked. The eight polyimide laminates correspond to the “first polyimide layer”.

[0241] According to Examples 1 to 4, it was confirmed that the insertion loss of the flexible metal-clad laminate decreases as the thickness of the polyimide laminate increases.

[0242] (Example 5)

[0243] A polyimide laminate was obtained by applying a thermoplastic polyamic acid solution to the film obtained in Synthesis Example 2, drying it, and heating it in the same manner as in Example 1. Furthermore, a test piece of a flexible metal-clad laminate was prepared under the same lamination conditions as in Example 1 and using the same copper foil as in Example 1.

[0244] (Comparative Example 1)

[0245] A test piece of a flexible metal-clad laminate was prepared in the same manner as in Example 1 except that only one polyimide laminate having a total thickness of 25.0 μm obtained in Example 1 was used and the thickness of the polyimide laminate was changed to 25 μm. The polyimide laminate corresponds to the “first polyimide layer”.

[0246] (Comparative Example 2)

[0247] A test piece of a flexible metal-clad laminate was prepared in the same manner as in Example 1 except that two polyimide laminates having a total thickness of 25.0 μm obtained in Example 1 were stacked and the thickness of the polyimide laminate was changed to 50 μm. The two polyimide laminates correspond to the “first polyimide layer”.

[0248] According to Example 1 and Comparative Examples 1 and 2, it was confirmed that the insertion loss of the flexible metal-clad laminate deteriorated (the absolute value increased) as the thickness of the polyimide laminate decreased.

[0249] (Comparative Example 3)

[0250] Three polyimide laminates having a total thickness of 25.0 μm were stacked in the same manner as in Example 2 except that the film obtained in Synthesis Example 3 was used, thereby preparing a test piece of a flexible metal-clad laminate.

[0251] According to Example 2 and Comparative Example 3, it was confirmed that if a polyimide laminate with large dielectric loss is used, the insertion loss of the flexible metal-clad laminate will deteriorate. In addition, according to Example 1 and Comparative Example 3, if a polyimide laminate with large electrical loss is used, the insertion loss of the flexible metal-clad laminate will deteriorate even if the thickness of the laminate is thick. According to the above results, in order to obtain good insertion loss, it is essential to use a polyimide laminate with small dielectric loss and laminate it thicker.

[0252] The dielectric constants and dielectric loss tangents of the flexible metal-clad laminates (multilayer polyimide films) obtained in Examples 1 to 5 and Comparative Examples 1 to 3, and the peel strength of the double-sided FCCL obtained from the polyimide film are shown in Table 1. Table 1 also shows the transmission loss measurement results at 10 GHz measured using the double-sided FCCL and the FPC test piece obtained under the above conditions.

[0253] [Table 1]

[0254] Dielectric constant Dielectric loss tangent Thickness(μm) Peel strength (N / cm) Insertion loss(dB)@10GHz Example 1 3.1 0.008 75 12.4 -2.4 Example 2 3.1 0.008 100 12.1 -2.1 Example 3 3.1 0.008 150 11.4 -1.8 Example 4 3.1 0.008 200 10.3 -1.6 Example 5 3.2 0.006 75 12.1 -2.2 Comparative Example 1 3.1 0.008 25 14.3 -4.5 Comparative Example 2 3.1 0.008 50 13.5 3.0 Comparative Example 3 3.3 0.018 100 11.7 -3.4

[0255] <Flexible Metal-Clad Laminate with Stripline Structure>

[0256] (Example 6)

[0257] After the thermoplastic polyamic acid solution was diluted with DMF to a solid content concentration of 10% by weight, the polyamic acid was applied to one side of the film obtained in Synthesis Example 1 using a comma coater so that the final single-side thickness was 4 μm, and heated in a drying oven set at 140° C. for 1 minute. The other side was also coated with polyamic acid in a manner such that the final thickness was 4 μm, and then heated in a drying oven set at 140° C. for 1 minute. Then, heat treatment was performed in a far-infrared heating oven at an atmosphere temperature of 360° C. for 20 seconds to obtain a polyimide laminate with a total thickness of 25.0 μm. Furthermore, the copper foil / 3 polyimide laminates with a total thickness of 25.0 μm / copper foil were stacked in the order of copper foil / 3 polyimide laminates with a total thickness of 25.0 μm / copper foil, and heat laminated using a hot roll laminator at a lamination temperature of 360° C., a lamination pressure of 0.6 tons, and a lamination speed of 1.0 m / min to produce a double-sided copper clad laminate (double-sided FCCL) (copper foil: CF-T49A-HD2, Ra=0.15 μm, thickness of polyimide laminate: 75 μm). The 3 polyimide laminates correspond to the "first polyimide layer" described above.

[0258] In addition, three sheets of copper foil / polyimide laminates with a total thickness of 25.0 μm were stacked in this order and heat-laminated using a hot roll laminator at a lamination temperature of 360° C., a lamination pressure of 0.8 tons, and a lamination speed of 1.0 m / min to produce a single-sided copper clad laminate (single-sided FCCL) (copper foil: CF-T49A-HD2, Ra=0.15 μm, thickness of polyimide laminate: 75 μm). The three sheets of the polyimide laminates correspond to the "second polyimide layer" described above.

[0259] One side of the double-sided FCCL containing the first polyimide layer is etched to produce a microstrip line with a line length of 10 cm, and the circuit part and the terminal part are copper-plated. The microstrip line circuit and the single-sided FCCL containing the second polyimide laminate are bonded together by means of a bonding sheet SAFY manufactured by NIKKAN INDUSTRIES Co., Ltd., and are heated under reduced pressure at 150°C for 30 minutes and 1 to 2 MPa. In this way, a test piece of a flexible metal-clad laminate with a stripline structure is produced. For the circuit width, the characteristic impedance is calculated based on the thickness, dielectric constant, and dielectric loss tangent of the constituent materials so that it becomes 50Ω. In order to reduce noise, the upper and lower grounding adopts a structure that is connected by through holes ( Figure 4 ).

[0260] (Example 7)

[0261] Test pieces of double-sided FCCL, single-sided FCCL and flexible metal-clad laminate were prepared in the same manner as in Example 6 except that four polyimide laminates having a total thickness of 25.0 μm obtained in Example 6 were stacked. The four polyimide laminates correspond to the “first polyimide layer”.

[0262] (Example 8)

[0263] Test pieces of double-sided FCCL, single-sided FCCL and flexible metal-clad laminate were prepared in the same manner as in Example 6 except that six polyimide laminates having a total thickness of 25.0 μm obtained in Example 6 were stacked. The six polyimide laminates correspond to the “first polyimide layer”.

[0264] (Example 9)

[0265] Test pieces of double-sided FCCL, single-sided FCCL and flexible metal-clad laminate were prepared in the same manner as in Example 6 except that 8 polyimide laminates having a total thickness of 25.0 μm obtained in Example 6 were stacked. The 8 polyimide laminates correspond to the “first polyimide layer”.

[0266] According to Examples 6 to 9, it was confirmed that the insertion loss decreased as the thickness of the polyimide laminate increased.

[0267] (Example 10)

[0268] The film obtained in Synthesis Example 2 was coated with a thermoplastic polyamic acid solution, dried, and heat-treated in the same manner as in Example 6 to obtain a polyimide laminate. Furthermore, using the same lamination conditions and the same copper foil as in Example 6, test pieces of double-sided FCCL, single-sided FCCL, and flexible metal-clad laminate were prepared.

[0269] (Comparative Example 4)

[0270] A test piece of a double-sided FCCL, a single-sided FCCL, and a flexible metal-clad laminate was prepared in the same manner as in Example 6 except that only one polyimide laminate having a total thickness of 25.0 μm obtained in Example 6 was used and the thickness of the first and second polyimide layers were each set to 25 μm. (Comparative Example 5)

[0271] Test pieces of double-sided FCCL, single-sided FCCL and flexible metal-clad laminate were prepared in the same manner as in Example 6 except that two polyimide laminates having a total thickness of 25.0 μm obtained in Example 6 were stacked and the thickness of the first and second polyimide layers was changed to 50 μm respectively.

[0272] It was confirmed from Example 6 and Comparative Examples 4 and 5 that the insertion loss deteriorated (the absolute value increased) as the thickness of the polyimide laminate was reduced.

[0273] (Comparative Example 6)

[0274] Three polyimide laminates having a total thickness of 25.0 μm were stacked in the same manner as in Example 6 except that the film obtained in Synthesis Example 3 was used to prepare test pieces of double-sided FCCL, single-sided FCCL, and flexible metal-clad laminate.

[0275] According to Example 7 and Comparative Example 6, it was confirmed that if a polyimide laminate with large dielectric loss is used, the insertion loss is deteriorated. In addition, according to Example 6 and Comparative Example 6, it can be seen that if a polyimide laminate with large dielectric loss is used, the insertion loss is deteriorated even if the thickness of the laminate is thick. According to the above results, in order to obtain good insertion loss, it is essential to use a polyimide laminate with small dielectric loss and to stack thicker.

[0276] The dielectric constants, dielectric loss tangents of the flexible metal-clad laminates (multilayer polyimide films) obtained in Examples 6 to 10 and Comparative Examples 4 to 6, and the peel strength of the double-sided FCCL obtained from the polyimide film are shown in Table 2. Furthermore, the transmission loss measurement results at 10 GHz measured using the double-sided FCCL and the FPC test piece obtained under the above conditions are shown in Table 2.

[0277] [Table 2]

[0278]

[0279] Description of Reference Numerals

[0280] 1. Ground plane

[0281] 2. The first polyimide layer

[0282] 3. Copper layer as signal line

[0283] 4. Second polyimide layer

[0284] 5. Adhesive layer 1

[0285] 6. Adhesive layer 2

[0286] 7. Single-sided flexible metal-clad laminate

[0287] 8. Adhesive layer (joining sheet)

[0288] 9. Double-sided flexible metal-clad laminate

[0289] 10. Non-thermoplastic polyimide

[0290] 11. Thermoplastic polyimide

Claims

1. A flexible metal-clad laminate, characterized in that: The flexible metal-clad laminate has a microstrip line structure, wherein the flexible metal-clad laminate has at least a signal line / a first polyimide layer / a ground layer in sequence, wherein the thickness of the first polyimide layer is 75 to 200 μm, and the dielectric loss at 10 GHz is less than 0.

008. The flexible metal-clad laminate further comprises a ground layer / a second polyimide layer / an adhesive layer, and at least comprises a ground layer / a second polyimide layer / an adhesive layer / a signal line / a first polyimide layer / a ground layer in this order. The second polyimide layer has a thickness of 100 to 200 μm and a dielectric loss of 0.008 or less at 10 GHz. The insertion loss of the flexible metal-clad laminate at 10 GHz is not less than -2.6 dB and not more than 0 dB, The first polyimide layer and the second polyimide layer each include a thermoplastic polyimide layer and a non-thermoplastic polyimide layer. The first polyimide layer and the second polyimide layer each have a three-layer structure including the thermoplastic polyimide layer on both sides of the non-thermoplastic polyimide layer. The first polyimide layer is a laminate of four or more polyimide films, the polyimide film having the three-layer structure and a thickness of 25 μm or more and less than 75 μm, The second polyimide layer is a laminate of three or more polyimide films, and the polyimide film has the three-layer structure and a thickness of 25 μm or more and less than 75 μm.

2. The flexible metal-clad laminate according to claim 1, characterized in that: The signal line is a copper layer, An adhesive layer is further provided between the copper layer and the first polyimide layer.

3. The flexible metal-clad laminate according to claim 1, characterized in that: There are two or more signal lines.

4. The flexible metal-clad laminate according to claim 1, characterized in that: The first polyimide layer comprises a thermoplastic polyimide layer and a non-thermoplastic polyimide layer. The non-thermoplastic polyimide layer is formed by imidizing polyamic acid. The polyamic acid uses an acid dianhydride compound and a diamine as raw material monomers.

5. The flexible metal-clad laminate according to claim 4, characterized in that: The acid dianhydride compounds are pyromellitic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)propane dianhydride, 1,1-bis(2 ,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)ethane dianhydride, oxydiphthalic dianhydride, bis(3,4-dicarboxyphenyl)sulfonic dianhydride, p-phenylene bis(trimellitic acid monoester anhydride), ethylene bis(trimellitic acid monoester anhydride), bisphenol A bis(trimellitic acid monoester anhydride), p-phenylene bis(trimellitic acid ester anhydride) or 2,2'-bis(4-(3,4-dicarboxyphenoxy)phenyl)propane dianhydride.

6. The flexible metal-clad laminate according to claim 4, characterized in that: The diamine is 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 4,4'-oxydiphenylamine, 3,3'-oxydiphenylamine, 3,4'-oxydiphenylamine, 4,4'-diaminodiphenyldiethylsilane, 4,4'-diaminodiphenylsilane, 4,4'-diaminodiphenylethylphosphine oxide, 4,4'-diaminodiphenyl N-methylamine, 4,4'-diaminodiphenyl N-phenylamine, 1,4-diaminobenzene (p-phenylenediamine), bis{4-(4-aminophenoxy)phenyl}sulfone, bis{4-(3 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone and 2,2-bis(4-aminophenoxyphenyl)propane, aliphatic diamines having 36 carbon atoms, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 4,4'-diamino-p-terphenyl, bis(4-aminophenyl)terephthalate or 2,2-bis(4-aminophenoxyphenyl)hexafluoropropane.

7. The flexible metal-clad laminate according to claim 1, characterized in that: The first polyimide layer comprises a thermoplastic polyimide layer and a non-thermoplastic polyimide layer. The thermoplastic polyimide layer is formed by imidizing polyamic acid. The polyamic acid uses an acid dianhydride compound and a diamine as raw material monomers.

8. The flexible metal-clad laminate according to claim 7, characterized in that: The acid dianhydride compounds are pyromellitic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)propane dianhydride, 1,1-bis(2 ,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)ethane dianhydride, oxydiphthalic dianhydride, bis(3,4-dicarboxyphenyl)sulfonic dianhydride, p-phenylene bis(trimellitic acid monoester anhydride), ethylene bis(trimellitic acid monoester anhydride), bisphenol A bis(trimellitic acid monoester anhydride), p-phenylene bis(trimellitic acid ester anhydride) or 2,2'-bis(4-(3,4-dicarboxyphenoxy)phenyl)propane dianhydride.

9. The flexible metal-clad laminate according to claim 7, characterized in that: The diamine is 4,4'-diaminodiphenyl ether, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 4,4'-oxydiphenylamine, 3,3'-oxydiphenylamine, 3,4'-oxydiphenylamine, 4,4'-diaminodiphenyldiethylsilane, 4,4'-diaminodiphenylsilane, 4,4'-diaminodiphenylethylphosphine oxide, 4,4'-diaminodiphenyl N-methylamine, 4,4'-diaminodiphenyl N-phenylamine, 1,4-diaminobenzene (p-phenylenediamine), bis{4-(4-aminophenoxy)phenyl}sulfone , bis{4-(3-aminophenoxy)phenyl}sulfone, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone and 2,2-bis(4-aminophenoxyphenyl)propane, aliphatic diamine having 36 carbon atoms, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 4,4'-diamino-p-terphenyl, bis(4-aminophenyl)terephthalate or 2,2-bis(4-aminophenoxyphenyl)hexafluoropropane.

10. The flexible metal-clad laminate according to any one of claims 1 to 9, characterized in that: The surface roughness (Ra) of the signal line on the first polyimide layer side is 0.05 μm to 0.5 μm.

11. A method for manufacturing a flexible metal-clad laminate, characterized in that: The flexible metal-clad laminate has a microstrip line structure, and the flexible metal-clad laminate at least has a signal line / a first polyimide layer / a ground layer in sequence. The flexible metal-clad laminate further comprises a ground layer / a second polyimide layer / an adhesive layer, and at least comprises a ground layer / a second polyimide layer / an adhesive layer / a signal line / a second polyimide layer / a ground layer in this order. The insertion loss of the flexible metal-clad laminate at 10 GHz is not less than -2.6 dB and not more than 0 dB, In the method for producing the flexible metal-clad laminate, a polyimide film having a thickness of 75 to 200 μm and a dielectric loss of 0.008 or less at 10 GHz is used as the first polyimide layer, and As the second polyimide layer, a polyimide film having a thickness of 100 to 200 μm and a dielectric loss of 0.008 or less at 10 GHz is used. The thermoplastic polyimide layer and the non-thermoplastic polyimide layer are laminated to form the first polyimide layer and the second polyimide layer, respectively. The first polyimide layer and the second polyimide layer each include the thermoplastic polyimide layer and the non-thermoplastic polyimide layer. The first polyimide layer and the second polyimide layer each have a three-layer structure including the thermoplastic polyimide layer on both sides of the non-thermoplastic polyimide layer. The first polyimide layer is formed by laminating four or more polyimide films, wherein the polyimide film has the three-layer structure and has a thickness of 25 μm or more and less than 75 μm. The second polyimide layer is formed by laminating three or more polyimide films, and the polyimide film has the three-layer structure and a thickness of 25 μm or more and less than 75 μm.

12. The method for manufacturing a flexible metal-clad laminate according to claim 11, characterized in that: The signal line is a copper layer, An adhesive layer is further provided between the copper layer and the first polyimide layer.

13. The method for manufacturing a flexible metal-clad laminate according to claim 11, characterized in that: The flexible metal-clad laminate has two or more signal lines.

14. The method for manufacturing a flexible metal-clad laminate according to claim 11, characterized in that: The first polyimide layer comprises a thermoplastic polyimide layer and a non-thermoplastic polyimide layer. The non-thermoplastic polyimide layer is formed by imidizing polyamic acid. The polyamic acid uses an acid dianhydride compound and a diamine as raw material monomers.

15. The method for manufacturing a flexible metal-clad laminate according to claim 14, characterized in that: The acid dianhydride compounds are pyromellitic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)propane dianhydride, 1,1-bis(2 ,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)ethane dianhydride, oxydiphthalic dianhydride, bis(3,4-dicarboxyphenyl)sulfonic dianhydride, p-phenylene bis(trimellitic acid monoester anhydride), ethylene bis(trimellitic acid monoester anhydride), bisphenol A bis(trimellitic acid monoester anhydride), p-phenylene bis(trimellitic acid ester anhydride) or 2,2'-bis(4-(3,4-dicarboxyphenoxy)phenyl)propane dianhydride.

16. The method for manufacturing a flexible metal-clad laminate according to claim 14, wherein: The diamine is 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 4,4'-oxydiphenylamine, 3,3'-oxydiphenylamine, 3,4'-oxydiphenylamine, 4,4'-diaminodiphenyldiethylsilane, 4,4'-diaminodiphenylsilane, 4,4'-diaminodiphenylethylphosphine oxide, 4,4'-diaminodiphenyl N-methylamine, 4,4'-diaminodiphenyl N-phenylamine, 1,4-diaminobenzene (p-phenylenediamine), bis{4-(4-aminophenoxy)phenyl}sulfone, bis{4-(3 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone and 2,2-bis(4-aminophenoxyphenyl)propane, aliphatic diamines having 36 carbon atoms, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 4,4'-diamino-p-terphenyl, bis(4-aminophenyl)terephthalate or 2,2-bis(4-aminophenoxyphenyl)hexafluoropropane.

17. The method for manufacturing a flexible metal-clad laminate according to claim 11, characterized in that: The first polyimide layer comprises a thermoplastic polyimide layer and a non-thermoplastic polyimide layer. The thermoplastic polyimide layer is formed by imidizing polyamic acid. The polyamic acid uses an acid dianhydride compound and a diamine as raw material monomers.

18. The method for manufacturing a flexible metal-clad laminate according to claim 17, wherein: The acid dianhydride compounds are pyromellitic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)propane dianhydride, 1,1-bis(2 ,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)ethane dianhydride, oxydiphthalic dianhydride, bis(3,4-dicarboxyphenyl)sulfonic dianhydride, p-phenylene bis(trimellitic acid monoester anhydride), ethylene bis(trimellitic acid monoester anhydride), bisphenol A bis(trimellitic acid monoester anhydride), p-phenylene bis(trimellitic acid ester anhydride) or 2,2'-bis(4-(3,4-dicarboxyphenoxy)phenyl)propane dianhydride.

19. The method for manufacturing a flexible metal-clad laminate according to claim 17, wherein: The diamine is 4,4'-diaminodiphenyl ether, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 4,4'-oxydiphenylamine, 3,3'-oxydiphenylamine, 3,4'-oxydiphenylamine, 4,4'-diaminodiphenyldiethylsilane, 4,4'-diaminodiphenylsilane, 4,4'-diaminodiphenylethylphosphine oxide, 4,4'-diaminodiphenyl N-methylamine, 4,4'-diaminodiphenyl N-phenylamine, 1,4-diaminobenzene (p-phenylenediamine), bis{4-(4-aminophenoxy)phenyl}sulfone , bis{4-(3-aminophenoxy)phenyl}sulfone, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone and 2,2-bis(4-aminophenoxyphenyl)propane, aliphatic diamine having 36 carbon atoms, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 4,4'-diamino-p-terphenyl, bis(4-aminophenyl)terephthalate or 2,2-bis(4-aminophenoxyphenyl)hexafluoropropane.

20. The method for producing a flexible metal-clad laminate according to any one of claims 11 to 19, characterized in that: The surface roughness (Ra) of the signal line on the first polyimide layer side is 0.05 μm to 0.5 μm.

Citation Information

Patent Citations

  • Fluorine-based resin containing polyimide precursor solution composition, polyimide and polyimide film using the same, and method for producing them

    JP2017078102A

  • Multilayer polyimide film

    JP2018145303A

  • Metal-clad laminate sheet and circuit board

    JP2018170417A

  • Method for manufacturing metal-clad laminate and method for manufacturing circuit board

    JP2020015237A